Chicken soup for the soul : here comes the bride: 101 stories of love, laughter, and family - Canfield, Jack , 1944-; Hansen, Mark Victor; Heim, Susan M. (Cos Cob, Connecticut : Chicken Soup for the Soul Publishing, 2012)
A collection of 101 true personal stories from brides, grooms, family, and friends, about proposals, engagements, wedding planning, weddings, and honeymoons. Includes brides of all ages and second marriages. Stories range from funny to heartwarming and cover the whole range of topics relating to becoming a bride and a newlywed
1. The proposal -- 2. The ring -- 3. The dress -- 4. It's all in the planning -- 5. Meet the parents -- 6. The wedding party -- 7. Martial mishaps -- 8. Bucking tradition -- 9. Never too late for love -- 10 The honeymoon
Keywords: Brides -- Anecdotes; Brides -- Literary collections; Marriage -- Literary collections; Marriage -- Anecdotes